Green and biomass-derived materials with controllable shape memory transition temperatures based on cross-linked Poly(l-malic acid). (10th October 2019) - Qiu, Yaxin; Wanyan, Qianru; Xie, Wenyuan; Wang, Zhifeng; Chen, Ming; Wu, Defeng
Abstract: An interesting biomass-derived shape memory polymer (SMP) based on cross-linked poly(l -malic acid) (PMA), with reconfigurable permanent shape and tunable shape memory transition temperature ( T trans ), was developed in this work. The amorphous cross-linked network was constructed in PMA using eco-friendly 1, 8-octanediol as the cross-linker through a catalyst-free two-step way. The relations between crosslinking density ( d ) and glass transition temperature ( T g ), as well as the mechanical strengths of as-obtained cross-linked PMA (CPMA) were then evaluated. Both the strengths and the T trans are easily tunable by controlling curing times. Moreover, the permanent shape of CPMA is reconfigurable due to additional crosslinking in the heat treatment process. It also shows good diversity of processing approaches. This work is the first report to achieve good strengths on the biodegradable PMA and to activate its shape memory effect, opening up a window of application of PMA as the smart material or even as the common plastics. Graphical abstract: Image 1 Highlights: Developing a green and very simple SMP based on the cross-linked PMA. The permanent shape is reconfigurable because of the solid state plasticity. Shape memory transition temperature is tunable by controlling curing times.